2010
DOI: 10.4049/jimmunol.1000526
|View full text |Cite
|
Sign up to set email alerts
|

TLR2 Is One of the Endothelial Receptors for β2-Glycoprotein I

Abstract: During the antiphospholipid syndrome, β2-gpI interacts with phospholipids on endothelial cell (EC) surface to allow the binding of autoantibodies. However, induced-pathogenic intracellular signals suggest that β2-gpI associates also with a receptor that is still not clearly identified. TLR2 and TLR4 have long been suspected, yet interactions between TLRs and β2-gpI have never been unequivocally proven. The aim of the study was to identify the TLR directly involved in the binding of β2-gpI on EC surface. β2-gpI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(55 citation statements)
references
References 57 publications
(61 reference statements)
1
52
0
1
Order By: Relevance
“…Moreover, ex vivo studies suggest a role for TLR2 [32][33][34], CD14 [34], GPIbα [35] and TLR8 [36] in aPLA-activated monocytes and EC. Below the role of each receptor/co receptor is described in more detail.…”
Section: Candidate Receptors For Aplamentioning
confidence: 99%
“…Moreover, ex vivo studies suggest a role for TLR2 [32][33][34], CD14 [34], GPIbα [35] and TLR8 [36] in aPLA-activated monocytes and EC. Below the role of each receptor/co receptor is described in more detail.…”
Section: Candidate Receptors For Aplamentioning
confidence: 99%
“…11 Moreover, a role for additional receptors such as TLR2 23,24 and apoER2 21,25,26 in anti-␤ 2 GPImediated EC activation and/or thrombosis has been reported. To address the roles of these receptors in the activation of ECs by anti-␤ 2 GPI Abs, we first transfected cells with siRNA specific for TLR4 or TLR2 or random sequence RNA of identical composition (control); each of the specific siRNAs inhibited the expression of target proteins, whereas the control RNA had no effect.…”
Section: Sirna-mediated Inhibition Of Tlr4 Expression Inhibits Apla/amentioning
confidence: 99%
“…Several groups showed that TLR2 but not TLR4 is involved in aPL-mediated cell activation (Satta et al, 2007(Satta et al, , 2011Alard et al, 2010), and a single group report has been published on the direct binding of b2GPI to TLR2 (Alard et al, 2010). By contrast, two groups reported that siRNA-mediated inhibition of TLR2 expression on ECs or anti-TLR2 blocking antibody pretreated monocytes did not affect the aPL-induced pro-coagulation state, suggesting that TLR2 may play a limited role in the activation of unperturbed cells (Lambrianides et al, 2010;Allen et al, 2012).…”
Section: Open Questionsmentioning
confidence: 96%
“…However, in vitro and in vivo experimental models highlight that TLR4 only partially contributes to the thrombogenic effect of aPL, suggesting that more than one receptor may be involved in b2GPI cellular binding. The main candidate receptors for b2GPI on cell membranes have been identified as TLR2, megaline, apolipoprotein Ereceptor2′ (ApoER2′), glycoprotein Iba (GPIba) and platelet factor 4 (PF4) (Kobayashi Review ª 2013John Wiley & Sons Ltd et al, 2001Shi et al, 2006;Alard et al, 2010;Sikara et al, 2010;Romay-Penabad et al, 2011).…”
Section: Open Questionsmentioning
confidence: 99%